APLIKASI MOBILE UNTUK PERPUSTAKAAN PADA SMAN 63 JAKARTA SELATAN - Sejati Waluyo (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2013)
Communications is technology is growing very rapidly as more public demand for technology, one o the technologies the mobile phone or the more familiar with the digital cellular phone or mobile phone. Now the mobile phone is an item that already owned by almost every element society. One of the features offered in the moblie phone to communicate than ie sms conversations. SMS is one medium that widely used, because sms has very cheap rate as compared to voice services or other services for communicating to the destination number. Never previously, imagined by the public that sms can used more as a medium of interpersonal communication in the form of text, but now people are able to use the sms service to the needs of the informastion in small capacity, for example, to find information in the school library. This reseacrh will be applied on a system based information services sms library which serves to receive, process and send back an sms containing the brief information students needed automatically without any operator direct reply to sms messages that will be sent to the school. With this system students are expected to feel the ease in getting information adn so similarly the school can provide the best service without being bothered to providing a special operator who will reply to the sms, because system will reply to the sms that sent automatically.Keyword: Libraries, mobile phone, informastion systems based SMS services